TINJAUAN YURIDIS TERHADAP ALIRAN KEPERCAYAAN DIHUBUNGKAN DENGAN PASAL 29 AYAT 2 UUD 1945 - Yudianita, Feby; Indra, Mexsasai; Ghafur, Abdul (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
Indonesian is a country consisting of various ethnis groups and languages starting from Sabang to Merauke. Diversity and pluralism which exist in Indonesian has established a wide range of cultures and philosophy of life Indonesian. Therefore the founders of this country. Has thought and formulate how to unite cultures and philosophy of life is variegated into a single unit. Pancasila with the motto unity in diversity. Before religion enfered Indonesia, former Indonesian society has adapted a system of cult, some of which are animism and dynamism. Flow belief system is not only used in Indonesia alone, but almost the entire world community earlier. Evidence that the cult was once lived in Indonesian.This study uses a method used in this study of primary legal materials , ie materials materials science of law that are closely related to the problems studied, namely , the Constitution of 1945, Act No. 39 of 1999 on Human Rights . Secondary law material , namely legal materials that explain or discuss matters that have been investigated on the materials of primary law , the State of Law Books , Books on Human Rights, various papers , journals , newspapers , magazines , documents , and data from the internet relating to the law penelitian.Bahan Tertiary , ie materials that give an explanation of the ingredients of primary and secondary law , namely Indonesian Dictionary and Dictionary of Law.The first study results , is the existence of cult pursuant to Article 29 paragraph 2 of the Constitution of 1945. Second , the factors difficulty cult gained recognition from the state . Third , an ideal concept cult pursuant to Article 29 paragraph 2 of the 1945 Constitution Suggestion writer , First , synchronize the legislation relating to religious freedom so that communities are able to implement the values of diversity to strengthen the morale of the nation . Secondly , should get a clear recognition of the state . Third , the state is not entitled to restrict and prohibit every citizen.Keywords : Judicial -Review - Beliefs